Enhancing Civic Activism Through the Re-Use of Public Information - Jabłoński, Mariusz (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The article analyses the scope of realization of the rights to access and to re-use public information in Poland. It characterizes the subject of this right and the key aspects of statutory regulation of the request procedure, which materialize the content of Article 61 of the Constitution of Poland. In its main section, the article provides an overview of newly-adopted provisions concerning the right to re-use public information and their potential impact on civic activity. This right enables a broad category of interested persons to obtain and use public information not only for informational and oversight purposes, but also for tangible and intangible gains.
Keywords: prawo dostępu do informacji publicznej; aktywność obywatelska; ponowne wykorzystywanie informacji publicznej; Polska